Chemical characterization of atmospheric particulate matter and source apportionment in an urban-industrial area of the Lisbon Metropolitan Area (Portugal) - Gamelas ou Carla A. Gamelas, Carla (2022)
Trabalho apresentado em 11th International Aerosol Conference (IAC2022), 4-9 de setembro 2022, Atenas, Grécia